1983
DOI: 10.1007/bf01311311
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a bovine origin of the polyomaviurs detected in foetal rhesus monkey kidney cells, FRhK-4 and -6

Abstract: Rabbit antisera to the stump-tailed macaque polyomavirus (STMV) which had been shown by immunoelectron microscopy and indirect immunofluorescence to react with the polyomavirus found in FRhK-4 cells (FRKV), also gave precipitin lines in counter-immunoelectrophoresis (CIE) and double diffusion in gel (GD) when reacted with FRKV. The reactions in GD showed identity with that of a rabbit antiserum to FRKV. Naturally occurring antibody to FRKV (anti-FRKV) was found by CIE in 48 per cent of 353 cattle, 1/106 pigs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Initial observations indicating a bovine rather than a monkey origin for these isolates came from two independent reports (Parry et al, 1983b;Wognum et al, 1984). These reports indicated that specific antibodies against these viral isolates were present in a high percentage of cattle sera and colostrum samples.…”
Section: Introductionmentioning
confidence: 99%
“…Initial observations indicating a bovine rather than a monkey origin for these isolates came from two independent reports (Parry et al, 1983b;Wognum et al, 1984). These reports indicated that specific antibodies against these viral isolates were present in a high percentage of cattle sera and colostrum samples.…”
Section: Introductionmentioning
confidence: 99%
“…BPyV sequences have been reported by diverse authors to be found in calf serum batches (24,32,38,39). Although antibodies have been detected in cattle (32,44) and in humans in close contact with cattle (31), no specific illness has been attributed to BPyV.…”
mentioning
confidence: 99%
“…Monkeys are already known to be the hosts of three different polyomaviruses: simian virus 40 [15], simian agent 12 [1,7,17] and lymphotropic papovavirus (LPV) [19], and another possible source of a polyomavirus is fetal calf serum used in the culture medium [11]. Indeed the bovine polyomavirus has been found as an adventitious virus in a number of different cell lines derived from primate kidney cultures [ 11,12,18].…”
Section: Discussionmentioning
confidence: 99%